An Evaluation of CGIAR Centers' Impact Assessment Work on Irrigation and Water Management Research - Merrey, Douglas J. (CGIAR Independent Science and Partnership Council, 2015)
A significant proportion of CGIAR research investment has been spent on policy and natural resource management (NRM). However, compared to other areas of research e.g., crop germplasm improvement (CGI), there appears to be relatively few impact assessments (IAs) in this domain. To fill this gap, one of the activities of the Standing Panel on Impact Assessment (SPIA)-coordinated Strengthening Impact Assessment in the CGIAR (SIAC) program targets assessments of these presumably ‘under-evaluated areas’ of CGIAR research, including irrigation and water management, agroforestry, and policy and social sciences.